Asymmetric flow field flow fractionation (AF4) of polymers with focus on polybutadienes and polyrotaxanes - Makan, Ashwell Craig (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)-- Stellenbosch University, 2012.